Continuous and long‐term treatment is more important than dosage for the protective effect of thiazide use on bone metabolism and fracture risk. (30th July 2015) - Kruse, C.; Eiken, P.; Vestergaard, P.
Abstract: Background: Data from observational studies have suggested that thiazide diuretics protect against fractures. Few studies have investigated time frames from initiation of treatment to fracture occurrence. Objective: To evaluate the time to spinal, hip, femur, wrist and upper extremity fracture occurrence before and after thiazide exposure. Methods: A matched retrospective cohort study of patient information from national Danish patient databases was conducted. Patients with reimbursed prescriptions for noncompounded thiazide diuretics with potassium supplementation (Anatomical Therapeutic Chemical classification system code C03AB) between 1996 and 2011 were matched with nonexposed control subjects by date of birth and gender. Weekly odds ratios (ORs) of fracture occurrence and total incidence rates (IRs) and incidence rate ratios (IRRs) of fracture risk were calculated for the periods before treatment initiation, weeks 1–42 and weeks 43–780. Results: A total of 1 602 141 'thiazide exposure periods' (46 8271 individuals) and 1 530 233 'nonexposure periods' (655 399 individuals) were included in the analysis. Thiazide use was associated with factors of increased de novo fracture risk. Weekly adjusted fracture risk between exposure and nonexposure was increased prior to commencing thiazide therapy, further increasing from weeks 1–42 weeks and then decreasing gradually from weeks 43–780. There was a decreasing trend in total age‐adjusted risk during these periods: IRR [95% confidence interval 1.44 [1.42; 1.47], 1.27 [1.24; 1.29] and 1.14 [1.11; 1.18], respectively. Prescription patterns showed several treatment breaks amongst thiazide users. Conclusions: It appears that thiazides reduce the background risk of fracture that is increased prior to commencing therapy. Long duration and continuity of thiazide exposure seems to be important to obtain this protective effect on fracture risk, but we have found in this study that this approach is not always used in clinical practice.